A new HLA‐C allele, HLA‐C*15:144, identified in a Chinese family. (4th April 2019) - Ai, Xiaofei; Wang, Jiying; Zhang, Yan; Li, Qinghua; Wang, Xiaojing
Abstract : HLA‐C*15:144 differs from HLA‐C*15:07 (343G‐>A, G91R).